2021
DOI: 10.1111/plb.13347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and yeast two‐hybrid provide new evidence for unique sporophytic self‐incompatibility system of Corylus

Abstract: Ping'ou hybrid hazelnut (C. heterophylla Fisch. 9 C. avellana L.); pistil-pollen interactions; quantitative real-time PCR (qRT-PCR); RACE cloning; yeast two-hybrid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…It is believed that the SRK-SCR recognition via phosphorylation and degradation facilitates the pollen‒pistil interaction ( Gu et al, 1998 ; Goring et al, 2014 ) and the SI signal transducers include SRK, SLG, SCR/SP11, and MLPK ( Takasaki et al, 2000 ; Takayama et al, 2000 ; Murase et al, 2004 ; Kakita et al, 2007b ; Kitashiba and Nasrallah, 2014 ). Nevertheless, SRK-ARC1 interaction was not functioning in Corylus , indicating that the SSI system was distinct between Corylus and Brassica ( Hou et al, 2022 ). Additionally, the Fagopyrum genome did not contain SRK or SLG ( Banović et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the SRK-SCR recognition via phosphorylation and degradation facilitates the pollen‒pistil interaction ( Gu et al, 1998 ; Goring et al, 2014 ) and the SI signal transducers include SRK, SLG, SCR/SP11, and MLPK ( Takasaki et al, 2000 ; Takayama et al, 2000 ; Murase et al, 2004 ; Kakita et al, 2007b ; Kitashiba and Nasrallah, 2014 ). Nevertheless, SRK-ARC1 interaction was not functioning in Corylus , indicating that the SSI system was distinct between Corylus and Brassica ( Hou et al, 2022 ). Additionally, the Fagopyrum genome did not contain SRK or SLG ( Banović et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed secretion and pollen adhesion on the stigma surface and blue fluorescence on the papillae within 60 min after compatible and incompatible pollination. While in incompatible pollination, bunched, short, or bulbous pollen tubes which do not penetrate the stigmatic surface were observed after 4 h ( Li, 2020 ; Hou et al, 2022 ). These observations suggested that pollen adhesion, hydration, and penetration of pollen tube are the earliest steps blocked in self-incompatible pollination.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither is located on LG5. Recently, also from “ Dawei ,” Hou et al (2022) identified five genes ( ChaTHL1 , ChaTHL2 , ChaMLPK , ChaARC1 , and ChaEX70A1 ), homologous to those participating in the downstream SSI response of Brassica . However, the expression and two-hybrid yeast assay analyses suggested the downstream signaling-pathway (SRK–ARC1 interaction) as the Brassica SSI response was not conserved in Corylus .…”
Section: Introductionmentioning
confidence: 99%
“…Several genes encoding RLKs have been identified at the S -locus (e.g., MIK2 and Putative Interactor of XopAC 7 [ PIX7 ]) ( Hill et al., 2021 ; Hou et al., 2022a ). Expression analyses and yeast two-hybrid assays confirmed that Corylus does not employ the SRK-mediated signaling pathway of Brassica SSI ( Hill et al., 2021 ; Hou et al., 2022a , 2022b ). Recent phylogenetic analysis provided additional evidence supporting the genus-specific evolution of SSI in Corylus , which is not shared by other members of Betulaceae ( Brainard et al., 2023 ).…”
Section: Molecular Basis Of Self-pollen Rejection In Different Si Sys...mentioning
confidence: 90%